High-Rate Altimetry in SNR-Based GNSS-R: Proof-of-Concept of a Synthetic Vertical Array - Yamawaki, M. K.; Geremia-Nievinski, F.; Monico, J. F.G. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Global Navigation Satellite System Reflectometry (GNSS-R) has emerged as a promising remote sensing technique for coastal sea level monitoring. GNSS-R based on signal-to-noise ratio (SNR) observations employs a single antenna and a conventional receiver. It performs best for low elevation satellites, where direct and reflected radio waves are very similar in polarization and direction of arrival. One of the disadvantages of SNR-based GNSS-R for sea level altimetry is its low temporal resolution, which is of the order of 1 h for each independent satellite pass. Here, we present a proof-of-concept based on a synthetic vertical array. It exploits the mechanical movement of a single antenna at a high rate (about 1 Hz). SNR observations can then be fit to a known modulation, of the order of the antenna sweeping rate. We demonstrate that centimetric altimetry precision can be achieved in a 5-min session.
Keywords: Altimetry; Antennas; Global navigation satellite system; Global Navigation Satellite System (GNSS); GNSS reflectometry (GNSS-R).; Satellite antennas; Satellites; Signal to noise ratio; Surface waves